Cooperação na administração pública: uma análise dos convênios e parcerias celebradas em uma instituição federal de ensino superior sob as perspectivas do Balanced Scorecard. - Gomes, Danilo Monteiro (2013)
Building relationships between organizations is a way to improve the productive process through the innovation that comes from partnership. Given the big amount and the speed in which convening are celebrated, many organizations, especially the ones of the public sector do not consider the possibility of finding a strategic positioning to the process of formalization of convening and partnerships. This research is grounded on the basic principle of Balanced Scorecard BSC (KAPLAN; NORTON, 2000) to positively influence people s behavior by showing them the organizational strategy in order to achieve the general objective of this dissertation which is use this tool for the characterization of multiple projects developed at a Federal Higher Education Institution (IFES). The method of descriptive investigation was adopted with a quanti-qualitative approach combined with participative observation to analyze 312 documents and present an unknown reality of the Universidade Federal da Paraíba (UFPB) that made it possible to comprehend a set of administrative and collaborative tools in which the institution was involved from 2007 to 2012. The results showed tendencies for themes linked to issues such as teaching, research, extension, end-activities, and consequently, the de-consideration of strategic objectives with higher capacity to promote the organizational development.